Leveraging anatomy to improve safety and efficacy in temple augmentations—a case series of 20 patients - Bravo, Bruna S. F.; Gonçalves Bravo, Leonardo; Gouvea, Bárbara Fouraux; Alves, Gabriel L. T. (Frontiers in Surgery, 2025)
IntroductionTemple augmentation has become a cornerstone in full-face aesthetic rejuvenation, yet traditional techniques often face limitations, including aesthetic limitations and the risk of vascular complications. This study explores a novel interfascial injection technique, aiming to improve both the safety and efficacy of soft tissue fillers in the temporal region by leveraging anatomical knowledge.Materials and methodsA total of n = 20 female patients, aged 26–75, received injections using Ultra Volume Rennova®, a high-viscoelastic dermal filler. The filler was administered with a 22G × 5 cm cannula into the interfascial plane, located between the superficial and deep temporal fascia. Ultrasound imaging was used to confirm accurate filler placement. The access point for injections was the infrazygomatic arch, targeting the anterior third of the temporal region.ResultsFavorable outcomes in terms of volumization and lifting effects in the upper third of the face were reported in all patients. Fifteen patients reported mild pain post-injection, and two reported moderate pain, with no serious adverse events or hematomas observed.ConclusionThis interfascial injection technique offers a safer and more effective alternative to traditional subcutaneous or supraperiosteal methods. By leveraging the anatomical relationship between the zygomatic arch and the deep temporal fascia, the procedure reduces the risk of vascular complications while achieving natural and lasting aesthetic results. Further studies are warranted to validate these findings and assess long-term outcomes.